The Organizational Communication Climate Human Relations Based in Facing the Industry 4.0 - Dudung Juhana; Kadir Kadir (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2020)
The development of information technology in Industry 4.0 has an impact on changes in organizational climate. This change in organizational climate causes changes in the interaction patterns of organizational members. This study aims to determine how the image of organizational communication climate after changes in Tendik's career patterns for the human relations approach. The survey method was conducted by involving 325 respondents for 3 (three) months. The results of the analysis show that the organizational communication climate is still below positive, meaning that education personnel generally have a perception that is above neutral towards the communication climate that develops in the organization. Managerial implications need interaction intensity, which will further encourage leadership to appreciate the achievement of work targets achieved by subordinates to motivate employees to improve competence further and provide excellent performance.